World Econonomic and Financial Surveys, 1987 : International Capital Markets. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1987)
This paper provides an assessment of trends in the international capital markets, including most notably recent market shocks to the financial system and developments in the debt situation. It also reviews the scope of progress achieved over the last few years in strengthening the financial system. Given the extensive changes that have taken place in domestic and international financial markets, the authorities in all industrial countries have begun to adapt their supervisory and regulatory framework to reflect better the new financial environment. These efforts acquired added importance with the recent financial market shocks. The outlook for lending to developing countries that have experienced payments difficulties has deteriorated during the past year. For most of these countries, the prospect for a resumption of spontaneous general purpose bank lending appears very limited. In gauging the vulnerability of the financial system, it should be borne in mind that adverse economic circumstances affecting sovereign loans could have a simultaneous, negative impact on domestic credit quality. In some countries, bank exposures to energy, agriculture, real estate, shipping, and elements of heavy industry remain problematic.